Construction contractor prequalification from polish clients’ perspective - Plebankiewicz, Edyta (Journal of Civil Engineering and Management, 2010)
A competent construction contractor is one of the indispensable conditions of a proper process and completion of a construction project. The article presents analysis results of the main criteria considered by Polish public clients in contractor competence evaluation. Research was carried out on the basis of demands stated by clients in restricted tenders announced in 2007. The author also presents research results of the methods and criteria for construction contractor selection, used by Polish private clients. To carry out the research a questionnaire was sent to 27 private clients at the turn of 2006/2007. The results of the research show that public clients in most of the restricted tenders use just one of the criteria used to qualify a candidate to the second stage of tender procedure and it is usually the contractor’s experience. Generally, it is characterised by the number of realised projects similar to the ordered one. For private clients, in contractor competence evaluation, technical possibilities of a contractor are especially valued. Experience in similar investments realisation, their quality, the equipment owned, and the staff are the top qualities in the rankings. Appreciated, although to a smaller extent, is also financial reliability of a contractor. Yet, criteria connected with project management are those which are the least valued ones. Published Published Online: 14 Oct 2010